A mídia dos outros somos nós: a experiência audiovisual do Ponto de Cultura Cinema para Todos - Cunha, Sonia Regina Soares da (2012)
This research aims to identify the process of appropriation of audio visual (in digital video) for collective symbolic production (participatory video practice that expresses popular culture) in a socio-cultural context where the minorities are. Therefore, we based this study on the students‟ experience of the film and video workshops held by Cinema para Todos (Culture Point Cine for All), in Natal, RN. Culture Point is the basis of the project Programa Nacional de Cultura, Educação e Cidadania Cultura Viva (National Program of Culture, Education and Citizenship - Living Culture) of the Brazilian Ministry of Culture. In 2010, the Cine for All developed three film and video workshops in the state of Rio Grande do Norte (Northeastern of Brazil), in the municipalities of Açu, Lajes and São Gonçalo do Amarante, within a public policy project of socio-cultural inclusion. These three workshops are the focus of this empirical investigation. To support the analysis of this research we consider that the spaces of workshops are sites of the social practices origin, assuming they show the development of the changes of actions that generate new practices. In this socio-cultural context the students as interlocutors process the communicative culture mediation, where come from the logics of action (using digital video) to become a mediatic practice (video auto ethnographic). With the overall goal set and the field of investigative action delimited we considered the methodology of case study suitable for the observation of the object, because it is a phenomenon of modernity, occurring in a context of real life and with little or no control over events. Participant observation and interviews was also applied to this case study. The analytical theoretical support comes from the notion of mediation by Jesús Martín-Barbero and the concept of habitus by Pierre Bourdieu. The research found that a new way of communicating has been developing by this social group, and this reflects the technological change experienced by them. The auto ethnographic videos, short movies, reveal an allegorical trial of the mainstream media, because while they use the mainstream format, they rework the aesthetic, but without revising the history, in fact they proposing to retell the history of themselves full of colorful details and with richness of their forgotten popular culture.